Inhalation Antibiotics in Ventilator-associated Pneumonia (VAP): Drugs, Devices, and Evidence. Issue 4 (July 2016) - Hoek, Rogier A.S.; Gommers, Diederik A.M.P.J.; Melles, Damian C.; van Westreenen, Mireille; Hunfeld, Nicole G.M.; Fraaij, Pieter L.A.; Hoogsteden, Henk C.; Groeneveld, Johan A.B.J.; van der Eerden, Menno M.
Abstract : Ventilator-associated pneumonia (VAP) is still one of the most frequent nosocomial infections. It is associated with a prolonged intensive care unit and hospital stay, high mortality rates, and additional health care costs. Despite the availability of modern intensive care unit care and antibiotics, the overall clinical cure rate for VAP in randomized clinical trials is low, especially in the presence of multidrug-resistant gram-negative pathogens. Therefore, many clinicians explore the use of inhalation antibiotics in the treatment of VAP. This review focuses on the currently available inhalation antibiotics for VAP and different types of nebulizers for the administration of antibiotics.